There and turn back again: the application of phage serine integrases in eukaryotic systems - Sales, Thais Torquato; de Oliveira, Marco Antônio; Florentino, Lilian Hasegawa; Lima, Rayane Nunes; Rech, Elibio (Frontiers in Bioengineering and Biotechnology, 2025)
Serine integrases (Ints) have gained prominence and have been extensively used in Synthetic Biology due to their ability to modify DNA sequences. Ints are recombinases encoded by the phage genome and have been used to unidirectionally catalyze an insertion, excision, or inversion of a specific DNA sequence between the two attachment sites (att) attB (bacterial attachment site) and attP (phage attachment site). The entire process is highly specific and accurate; therefore, Ints are widely used in genetic engineering and have been extensively studied due to their unique site-specific recombination properties and potential genome editing applications. Furthermore, new recombinational factors (RDFs) and their determinants are constantly being discovered, underlining the need to update progress in research involving Ints in eukaryotic cells. In this way, this review aims to provide an overview of Ints in eukaryotic cells and highlight how Ints can be used in innovative ways to advance genetic engineering applications in health, agriculture, and environmental sciences.